2017
DOI: 10.1142/s0219633617500420
|View full text |Cite
|
Sign up to set email alerts
|

Withania somniferaphytochemicals confer neuroprotection by selective inhibition of nNos: Anin silicostudy to search potent and selective inhibitors for human nNOS

Abstract: Neuronal nitric oxide synthase (nNOS or NOS1) is an important therapeutic target for the treatment of various neurological diseases. A major challenge faced in the design of nNOS inhibitors emphasizes on potency in humans and selectivity over other NOS isoforms À À À eNOS and iNOS. The present structural-based in silico study was carried out to search potent and selective inhibitor for human nNOS from a set of 40 Withania somnifera phytochemicals structure. Ten phytochemicals appear as dual-selective inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…219 Through a structure-based in silico study, Kumar et al found that withanolide B is a potent and selective human nNOS inhibitor with the potential to act as an oral neurotherapeutic agent against neurological disorders. 220 In addition, Kumar et al reported that withanolide M might be a potent neurotherapeutic agent to combat neurological disorders mediated by nNOS and iNOS activation. 221 To identify new potential therapeutic targets of withanolide A for neurodegenerative diseases, Crane et al designed and synthesized molecular probes and found the glucocorticoid receptor (GR) as a potential target.…”
Section: Biological Activities and Mechanismsmentioning
confidence: 99%
“…219 Through a structure-based in silico study, Kumar et al found that withanolide B is a potent and selective human nNOS inhibitor with the potential to act as an oral neurotherapeutic agent against neurological disorders. 220 In addition, Kumar et al reported that withanolide M might be a potent neurotherapeutic agent to combat neurological disorders mediated by nNOS and iNOS activation. 221 To identify new potential therapeutic targets of withanolide A for neurodegenerative diseases, Crane et al designed and synthesized molecular probes and found the glucocorticoid receptor (GR) as a potential target.…”
Section: Biological Activities and Mechanismsmentioning
confidence: 99%
“…The structures determined by the X-ray diffraction method at a resolution of 1.50 Å and 2.01 Å, respectively, have been previously reported [52,56]. Molecular docking preparation and simulation were performed using UCSF Chimera Version 1.14 and AutoDock 4.2 [57][58][59][60]. UCSF Chimera was loaded with the structure of FAD-containing ferredoxin-NADP reductase and type III effector XopAI for molecular docking preparation.…”
Section: Molecular Docking Studymentioning
confidence: 99%
“…The energy minimization of D4 receptor, phenothiazines derivatives (5a-d and 7) and antipsychotics were performed by UCSF Chimera according to Kumar et al[24]. The docking simulation was performed according to Kumar et al[25,26]. Briefly, a grid box, which comprises the entire binding pocket of D4 receptor including orthosteric binding pocket (OBP) and extended binding pocket (EBP) was generated that provides enough space for rotational and translational walk to the ligands.…”
mentioning
confidence: 99%